Treating patients with platinum-sensitive extensive-stage small-cell lung cancer in a real-world setting - Sands, Jacob; Subramanian, Janakiraman (Frontiers in Oncology, 2023)
Small-cell lung cancer (SCLC) is an aggressive disease with poor 5-year survival, particularly for patients with extensive-stage disease. Extensive-stage SCLC generally responds to first-line treatment with platinum plus etoposide with either atezolizumab or durvalumab. Second-line treatment and beyond for relapsed or refractory SCLC is more challenging. For patients who responded to platinum-based chemotherapy (relapse >6 months after treatment), rechallenge with the original or similar platinum-based regimen is the preferred treatment option per the NCCN Clinical Practice Guidelines in Oncology (NCCN Guidelines ® ) for SCLC; patients who relapse 3-6 months after treatment may also be considered for rechallenge. For patients with platinumresistant disease (relapse ≤6 months), the preferred regimen is not specified, but other recommended regimens approved by the US Food and Drug Administration include topotecan and lurbinectedin. Clinical trial participation is a preferred regimen, highlighting the need for improved options in this setting. Among the other NCCN-recommended regimens, we consider irinotecan, paclitaxel, and temozolomide most favorable, and discuss settings for particular consideration. Nivolumab or pembrolizumab can be considered for patients who did not receive an immune checkpoint inhibitor in the first-line setting. Clinical trials of various novel therapies are ongoing and should be discussed with patients who qualify for trial enrollment.